LITERACY-BASED PPKN POCKET BOOK DEVELOPMENT TO IMPROVE STUDENT LEARNING OUTCOMES OF CLASS IV SDN 067243 MEDAN SELAYANG DISTRICT, YEAR 2020/2021 - Ifran Fredy Tarigan; Reh Bungana Br.Perangin-Angin; Daulat Saragi (SENSEI RESEARCH CENTER, 2021)
This research is a type of research development (Research and Development) which aims to determine how the development of a Literacy-based PPKn pocket book, how the feasibility and effectiveness of the Literacy-based PPKn pocket book. The method used to analyze the data is a qualitative descriptive technique which is expressed in the distribution of scores and categories of the rating scale. This development research produces products that meet the eligibility requirements after validation by expert validators. material validation was declared very feasible with a percentage of 89.77%. For linguists it is stated very feasible with a percentage of 88%. and design experts are declared fit for use with a percentage of 80.76%. In this study, feasibility was also obtained from student response questionnaires after students used and ate the products that had been developed. The results of the student response questionnaire to the development of the Literacy-based PPKn pocket book were also said to be feasible with a percentage of 76.19%. The effectiveness of the product can be seen from the N-Gain value. From the N-Gain value of the experimental class reaching 0.48, it was stated that the effectiveness of the pocket book was in the Medium category. It is different from the control class which is categorized as low effectiveness with a score of 0.26. Furthermore, the researcher tested the research hypothesis, whether the hypothesis was acceptable or not using the t-test with the help of the SPSS program. In the output of the paired sample test with SPSS version 17, the Sig (2-tailed) value of 0,000 <0.05 was obtained, so according to the basis for decision making in the paired sample test it can be concluded that Ho is rejected and Ha is accepted, it can be concluded that the development of a pocket book Literacy-based PPKn is feasible and effective to use in grade IV SDN 067243 Medan Selayang District Year 2020/2021